The mental health impact of repeated COVID-19 enforced lockdowns in England: evidence from the UK Household Longitudinal Study - Rashpal K. Dhensa-Kahlon; Siu Tim Wan; Jacqueline A.-M. Coyle-Shapiro; Kevin Rui-Han Teoh (BJPsych Open)
Background Research shows initial COVID-19 lockdowns increased population mental distress. Yet, the mental health impact of repeated lockdowns in England remains unknown.